Synthesis of some selenacrown ethers and the thermodynamic origin of their complexation with C60 - Liu, Yu (2011)
Two new selenacrown ethers, i.e., N,N'-dimethyl-1,11-diaza-4,8,14,18,-tetraselenacycloicosane (1) and 7,11-